There is a difference in functional ankle stability between different types of footwear in male athletes: A cross-sectional study - Wagemans, J.; Kuppens, K.; Peeters, G.; Baert, I. (The Foot, 2020)
Highlights Athletes performing their sports barefoot perform better at clinical ankle stability tests than athletes performing their sports with footwear.